Skador av is och ytvatten i vall i norra Sverige - Lundberg, Marie (2002)
The anaerobe respiration of microorganisms and plants promotes production of toxic substrate like carbon dioxide and ethanol in both plant and soil. Ice and standing water limit the possibility for plants to exchange gases, which causes a deleterious situation for the plants. The problem of damage to plants during winter dormancy because of ice and standing water is a problem foremost in areas with flat topography and unstable winter climate (periods of freezing and thawing). The purpose of this study was to do an literature inventory of different types of damage in grassland during dormancy and to study the result from field experiment with surface drainage system and see if the system would reduce damage done by ice and standing water. The purpose was also to study the range of winter damage in grassland in the coastal area of Norrbotten and Västerbotten and to study different ways to overcome the problem at a number of selected farms. The problems with winter damage in grasslands in northern Sweden were investigated with help of a questionnaire. The inquiry was done among dairy farmers during the summer 200l. The literature review showed different factors causing winter damage in grassland. The different groups were farming, climate, biotic and plant physiologic factors. Expect for these four groups, the topography and the soil type also have an effect on the possibility for over wintering. Late last harvesting of silage, soil compaction and late supplying of nitrate fertilizer are farming factors that increase the risk of winter damage in grassland. Upfreezing of plants, standing water and ice in grassland are examples of c1imate factors causing winter damage in grassland. Fungi damage in grassland is a biotic problem. Deep snow cover that longs for a long time increase the risk of fungi damage in grassland. An example of plant physiologic is plant hardening. If the plant has a good hardiness the chance to overcome the winter problems increase. The conclusion of the field experiment could not give any ...